Acid sensing to inflammaging: mechanisms and therapeutic promise of GPR68 (OGR1) in aging-related diseases - Wei, Jianlei; Cui, Fengxin; Huang, Zhihua; Li, Zeping; Mao, Zebin; Zhang, Pengxia (Frontiers in Aging, 2025)
GPR68 is a proton-sensing G protein-coupled receptor with an activation threshold at extracellular pH values between 6.5 and 7.0. It is widely expressed in diverse cell types, particularly in fibroblasts and cancer cells, within inflammatory and tumor microenvironments. In inflammatory bowel disease patients, GPR68 expression is also significantly increased in macrophages and monocytes. GPR68 primarily modulates inflammatory responses through the Gq/11–phospholipase C–inositol 1,4,5-trisphosphate/Ca2+ signaling axis. Extracellular acidification first promotes GPR68 coupling with Gq/11, subsequently enhancing phospholipase Cβ activity and increasing IP3 production; IP3 then mediates Ca2+ release from the endoplasmic reticulum, activating calmodulin-dependent kinase and calcineurin, ultimately inducing NF-κB and NFAT nuclear translocation to upregulate inflammatory mediators such as IL-6, TNF-α, and COX-2. This cascade activates inflammatory signaling pathways, thereby driving cellular and tissue senescence and creating favorable conditions for the progression of age-related diseases. However, its long-term causal relationship requires further validation through prospective studies. Abnormal GPR68 expression is closely associated with chronic inflammation, acidosis, and fibrosis in diseases including osteoarthritis, atherosclerosis, chronic kidney disease, Alzheimer’s disease, Parkinson’s disease, glioblastoma (GBM), and pancreatic cancer. In GBM, knocking down GPR68 or using the GPR68 inhibitor ogremorphin significantly reduces tumor cell survival. Despite its potential as a therapeutic target, challenges remain, such as the unresolved crystal structure, the lack of in vivo causality, cell-type specificity, and context-dependent signaling mechanisms. Targeting GPR68 may offer novel therapeutic strategies for these pathological processes.